2018
DOI: 10.3758/s13414-018-1598-4
|View full text |Cite|
|
Sign up to set email alerts
|

Search efficiency is not sufficient: The nature of search modulates stimulus-driven attention

Abstract: It has long been debated whether or not a salient stimulus automatically attracts people's attention in visual search. Recent findings showed that a salient stimulus is likely to capture attention especially when the search process was inefficient due to high levels of competition between the target and distractors. Expanding these studies, the present study proposes that a specific nature of visual search, as well as search efficiency, determines whether or not a salient, task-irrelevant singleton stimulus ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Other studies demonstrated that salient goal-irrelevant distractors could attract the observer's attention, slowing down the search [13][14][15][16]. The large variability of the results reported in the literature supports the notion that a combination of factors affects human attention guiding when looking for a target [17].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Other studies demonstrated that salient goal-irrelevant distractors could attract the observer's attention, slowing down the search [13][14][15][16]. The large variability of the results reported in the literature supports the notion that a combination of factors affects human attention guiding when looking for a target [17].…”
Section: Introductionmentioning
confidence: 67%
“…The priority map is considered to combine the representation of bottom-up object's distinctiveness and its topdown relevance to the observer [84,85]. The impact of saliency in visual search guidance has been debated, where the contribution of saliency is apparent in some tasks at hand [13][14][15][16], but not in others [10][11][12]. The neurophysiological studies also demonstrate a varied saliency contribution in the priority map building across different tasks [84].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this theory, ample evidence has been found that a salient stimulus, even though it is task-irrelevant, captures attention (Theeuwes, 1992(Theeuwes, , 2004. However, a recent study, along with many other previous studies (Bacon & Egeth, 1994;Barras & Kerzel, 2017;Gaspelin, Ruthruff, & Lien, 2016;Lamy & Egeth, 2003), has shown that capture of attention by a salient stimulus does not always take place; the nature of the search task was found to be critical for observing stimulus-driven attentional capture (Jung, Han, & Min, 2019). In this study, when participants performed the orientation feature search task, a singleton distractor captured attention, whereas the salient distractor failed to capture attention under the Landolt-C search task.…”
mentioning
confidence: 81%
“…To address this issue, in the present study we tested whether memory-driven attentional capture is also dependent on how a given search is performed. As in our previous study (Jung et al, 2019), we employed two different visual search tasks whose underlying processes are known to be different: Landolt-C search and orientation feature search.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation